An investigation of stakeholder influence on participants’ informed consent in the monitoring and evaluation process - Kapay, Sara (My University, 2022)
Monitoring and Evaluations (hereafter referred to as evaluations) aid in decision making, come in many forms and have various functions depending on their objectives. The nature of evaluations is such that they are reliant on participation from various individuals, communities, and organizations. Informed consent is the process by which participants are made aware of the potential risks, benefits, and objectives of a study and thereafter formally or informally indicate their consent to take part in the proposed research. Informed consent is required as it contributes to trust amongst stakeholders in evaluations. However, while issues regarding informed consent (both in theory and practice) have a well-documented history, especially in medical journals that centre on developed nations; further insights still need to be garnered. As such, there is a need to understand the informed consent process and its suitability within low-income nations in research and evaluations. Consequently, this research report aims to provide an understanding of stakeholder influence on informed consent on participants in evaluations and how power and pressure mechanisms from stakeholders affect informed consent. The interviews allowed us to better understand the role of stakeholders and their influence in informed consent through the perspectives and lived realities of evaluators, industry experts, researchers, and academics as well as those currently working in organisations that have been evaluated. It is evident from the interview findings that the power dominance, pressure, and influences that occur in Evaluation can be both implied and explicit. There is no consensus on what constitutes true informed consent or what exactly and to what extent should participants be informed within evaluations. Rather the focus is more on the protection and privacy of information and data of the evaluations than participants' consent. The observed and dominant ways stakeholders influence participant informed consent is through information. This study contributes to the existing literature on the relationship between evaluators, participants, and decision-makers as well as the power dynamics experienced practically within evaluations. The researcher proposes that a more deliberate approach needs to be taken during the conception phase of evaluations. Finally, further research looking at participation in Evaluation from the lenses of participants is required. In addition, a deeper look into ethics within evaluations as service providers to their stakeholders.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Management to the Faculty of Commerce, Law and Management, Wits School of Governance, University of the Witwatersrand, Johannesburg, 2022
Keywords: Informed consent; Evaluations; Stakeholder influence; UCTD; Monitoring; Protection and privacy; Information and data; SDG-8: Decent work and economic growth